2012
DOI: 10.5937/scriptamed1201025k
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of keratoconus in candidates for refractive surgical procedures

Abstract: Introduction. Keratoconus is the most common primary ectasia and has a signifi cant effect on visual acuity and the quality of life. The prevalence of keratoconus in the general population of Bosnia & Herzegovina, and Croatia remains unknown. This study was designed to show the incidence of keratoconus in candidates for Excimer laser refractive surgical procedures in our eye clinics. Methods. We analyzed preoperative examination data from 2,714 patients, collected over a two year period, who were candidates fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…We are aware of only two other studies on refractive surgery populations in the region around N. Macedonia. The prevalence of KC in these studies was 2.9% and 8.5% respectively, values much lower compared with the current study [19,20]. However, the design of these other studies did not consider ethnicity and the age ranges in the sample groups were limited.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…We are aware of only two other studies on refractive surgery populations in the region around N. Macedonia. The prevalence of KC in these studies was 2.9% and 8.5% respectively, values much lower compared with the current study [19,20]. However, the design of these other studies did not consider ethnicity and the age ranges in the sample groups were limited.…”
Section: Discussioncontrasting
confidence: 63%
“…There are uncertainties concerning gender as a predisposing factor in the diagnosis of KC in the different refractive surgery populations around the world. Studies by Omer [17] and Talal et al [21] found the prevalence in males and females was about the same, but Kozomara et al [20] found slightly higher prevalence among males than females.…”
Section: Gendermentioning
confidence: 91%
“…[8][9][10][11][12][13][14] An increased number of patients with forme fruste keratoconus tend to seek laser vision correction; the incidence has been documented to be in some cases as high as 9%. 15 Fortunately, some years ago Spoerl, Huhle, and Seiler 16 published a procedure called corneal collagen cross-linking with ribofl avin that provided a partial solution to the problem of ectatic and keratoconic corneas. Studies from their institute and many others have advanced the fi eld with over 400 papers having been published since that time.…”
mentioning
confidence: 99%